Winner Takes All? The Blockbuster Effect on Crowdfunding Platforms - Wang, Zhiyi; Yang, Lusi; Hahn, Jungpil (Information Systems Research, 2023)
Blockbuster projects on crowdfunding platforms are those that have achieved outstanding and exceptional performance. Regarding the impact of blockbuster projects on crowdfunding platforms, there are two plausible yet opposing predictions: they may exhibit both a negative effect by monopolizing backer attention and resources and a positive effect by increasing the activeness of backer side. This tension could be further complicated, considering that blockbusters are inherently heterogeneous. Drawing on the cross-side network effects literature and integrating insights from the unique features of crowdfunding, we develop a theoretical framework highlighting the multidimensional view of blockbuster effects: blockbuster projects have an overall positive effect on the performance of concurrent projects (overall effect), and such positive effect is stronger for related blockbusters (local effect) and blockbusters emerging before the focal project (temporal effect). With data from a leading crowdfunding platform, the empirical analyses largely support our proposed framework. Using off-platform data and backer data, we unveil the mechanism driving the blockbuster effects: blockbusters increase the popularity of the platform, whereby backers participating in the blockbusters tend to develop positive impressions and heightened expectations, so that they are likely to participate in other concurrent projects. Our findings have important implications for project creators and platform operators.